New Alternaria solani Predictive Model Based on Artificial Neural Network - Thierry Marique; Maxime Bonnave; Cyrille Vryghem; Benjamin Couvreur; John Rivière; Olivier Mahieu; Deborah Lanterbecq (Potato Research, 2026)

Can natural language processing or large language models replace human operators for pre-processing word and sentence-based free comments sensory evaluation data? - Michel Visalli; Ronan Symoneaux; Cécile Mursic; Margaux Touret; Flore Lourtioux; Kipédène Coulibaly; Benjamin Mahieu (Food Quality and Preference, 2025)

Implementation of sample pooling to strengthen the self-monitoring in the food industry: Case study of mycotoxins in cereals - Jean-Michel Galharret; Benjamin Mahieu; Jérémy Ratel; Evangelia Krystalli; Katerina Pissaridi; Evelyne Vigneau; Erwan Engel (Food Research International, 2025)

Ohmic pasteurization of probiotic chocolate dairy desserts and its quality attributes - Gabriela R.A. Silva; Wanessa P. da Silva; Elson R. Tavares Filho; Louise de A. Sobral; Carolina P.C. Martins; Benjamin Mahieu; Jonas T. Guimarães; Maria Carmela K.H. Duarte; Mônica M. Pagani; Ramon Silva; Monica Q. Freitas; Eliane T. Mársico; et al. (Food Research International, 2024)

Comparison of open comments and check-all-that-apply to collect reasons for liking and disliking chocolates in preference mapping - Nicolas Antille; Fanny Audoubert; Matthieu Camilleri; Manon Grain; Andreas Rytz; Nicolas Pineau; Benjamin Mahieu (Food Quality and Preference, 2024)

Temporal precision and resolution of TDS and TCATA used with consumers - Michel Visalli; Benjamin Mahieu; Caroline Peltier; Sylvie Cordelle; Pascal Schlich (Food Quality and Preference, 2024)

Impact of adding xylooligosaccharides encapsulated in butter: Microstructural, optical, rheological and sensory aspects - Mariana C. Rosa; Benjamin Mahieu; Elson Rogério Tavares Filho; Rodrigo N. Cavalcanti; Manoela Martins; Louise A. Sobral; Celso Sant'Anna; Erick A. Esmerino; Rosana Goldbeck; Tatiana C. Pimentel; Marcia Cristina Silva; Adriano G. Cruz (Food Research International, 2023)

Hedonic valence of descriptive sensory terms as an indirect measure of liking: A preliminary study with red wines - Michel Visalli; Benjamin Mahieu; Magalie Dubois; Pascal Schlich (Food Quality and Preference, 2023)

Free comment as a valuable approach to characterize and identify the drivers of liking of high-protein flavored milk drink submitted to ohmic heating - Ramon S. Rocha; Benjamin Mahieu; Elson R. Tavares Filho; Patrícia B. Zacarchenco; Mônica Q. Freitas; Eliane T. Mársico; Tatiana C. Pimentel; Erick A. Esmerino; Adriano G. Cruz (Food Research International, 2023)

First steps towards FAIRization of product-focused sensory data - Michel Visalli; Pascal Schlich; Benjamin Mahieu; Arnaud Thomas; Magalie Weber; Elisabeth Guichard (Food Quality and Preference, 2023)

Soil organic matter biochemistry and potential susceptibility to climatic change across the forest‐tundra ecotone in the Fennoscandian mountains - SOFIE SJÖGERSTEN; BENJAMIN L. TURNER; NATHALIE MAHIEU; LEO M. CONDRON; PHILIP A. WOOKEY (Global Change Biology, 2003)
We studied soil organic carbon (C) chemistry at the mountain birch forest‐tundra ecotone in three regions of the Fennoscandian mountain range with comparable vegetation cover but contrasting degrees of continentality and latitude. The aim of the study was to identify functional compound classes and their relationships to decomposition and spatial variation across the ecotone and latitudinal gradient. Solid‐state 13 C nuclear magnetic resonance (CPMAS 13 C NMR) was used to identify seven functional groups of soil organic C: alkyls , N‐alkyls , O‐alkyls , acetals , aromatics , phenolics and carboxyls . N‐alkyls , O‐alkyls and acetals are generally considered labile substrates for a large number of saprotrophic fungi and bacteria, whilst phenolics and aromatics are mainly decomposed by lignolytic organisms and contribute to the formation of soil organic matter together with aliphatic alkyls and carboxyls . All soils contained a similar proportional distribution of functional groups, although relatively high amounts of N‐alkyls , O‐alkyls and acetals were present in comparison to earlier published studies, suggesting that large amounts of soil C were potentially vulnerable to microbial degradation. Soil organic matter composition was different at the most southerly site (Dovrefjell, Norway), compared with the two more northerly sites (Abisko, Sweden, and Joatka, Norway), with higher concentrations of aromatics and phenolics , as well as pronounced differences in alkyl concentrations between forest and tundra soils. Clear differences between mountain birch forest and tundra heath soil was noted, with generally higher concentrations of labile carbon present in tundra soils. We conclude that, although mesic soils around the forest‐tundra ecotone in Fennoscandia are a potential source of C to the atmosphere in a changing environment, the response is likely to vary between comparable ecosystems in relation to latitude and continentality as well as soil properties especially soil nitrogen content and pH.